Is real estate a real diversifier in Pakistan? An ARDL approach - Hafsa Rasheed; Habib Ahmad; Attiya Yasmin Javid; Idrees Khawaja (Cogent Business & Management, 2022)
Traditional assets, like stocks and bonds, are mostly found to be highly influenced by uncertainties, and cause distress for investors most of the time, consequently investors look for safe investment options that can provide diversification benefits to cope with uncertainties. So, current research unveils the diversification characteristics of real estate by investigating its relationship with a set of selected financial assets like KSE-100 index, gold, sub-asset classes; growth stocks, value stocks, large stocks, small stock, and sector's stock. Autoregressive distributive lag (ARDL) approach is employed on monthly time series data for a time span of 2011 to 2019. Findings indicate that real estate behaves quite differently than all of these assets and holds good diversification potential for Pakistani investors because it exhibits no relationship with any of the assets under study. Findings suggest that Pakistani investors must incorporate real estate in their asset allocation strategy for diversifying their portfolios. Current research contributes to literature by unveiling the diversification potential of real estate in comparison to a set of financial variables that are rarely investigated in previous literature. Moreover, it contributes well to the knowledge of Pakistani investors and asset/investment managers to make healthy investment decisions.
Keywords: 650; Pakistan; diversification; ARDL; gold; Real Estate; stocks